Modifications des paramètres physico-chimiques de l’eau marine, produites à la suite du mélange avec de fluides de forage - Șerbănescu, O.; Piescu, Victoria (Cercetări Marine - Recherches Marines, 2026)
The authors have studied the modifications of some physical and chemical parameters of sea water (pH, color, density, suspended materials, BOD, organic substance, nitrates, Fe+++, oil products) under the influence of 4 drilling fluids. Changes were observed especially on pH, organic substance content, phosphates, nitrates and BOD.